TV-tekster til tiden - oversættelse og tekstning af nyheder - Heine, Jytte (HERMES - Journal of Language and Communication in Business, 2017)
News subtitling for television in several ways differs from the subtitling of films on television: There is very short time available for the work, all foreign languages are translated from spoken language – like interpreting – and finally the subtitles are cued directly during transmission. The time problem becomes still more evident in connection with the traditional presubtitling in the national languages for people with hearing disabilities. To meet their demands for subtitled news broadcasts a couple of European countries have introduced simultaneous subtitling, a costly andn problematic solution.